2003
DOI: 10.1080/0892701021000030133
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influences ofPseudomonas aeruginosaandDesulfovibrio desulfuricanson their Adhesion to Stainless Steel

Abstract: The mutual influences of Pseudomonas aeruginosa PAO1 and Desulfovibrio desulfuricans subsp. desulfuricans (ATCC 29577) on their adhesion to stainless steel were investigated in batch and column experiments. It was found that P. aeruginosa promoted the adhesion of D. desulfuricans under conditions of turbulence, but not under quiescent conditions. The enhancement involved the alignment of most D. desulfuricans along P. aeruginosa cells and was attributed to the additional interaction surface area provided by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Upon comparison of bacterial retention behavior between the batch and column assays, we found that retention of the cells was much greater in the batch assays, with ␣ values two to three times higher in the batch compared to the column studies. This is in contrast to prior research, which has shown that bacterial transport is much greater under convective (column) conditions, compared to the quiescent conditions of a batch experiment (Medilanski et al, 2003;Rijnaarts et al, 1993). A possible explanation for the discrepancy is that the bacteria have a greater affinity for glass than for the sand grains, so hydrodynamics alone cannot account for the differences in retention behavior.…”
Section: Bacterial Retention In Batch and Column Assayscontrasting
confidence: 79%
See 1 more Smart Citation
“…Upon comparison of bacterial retention behavior between the batch and column assays, we found that retention of the cells was much greater in the batch assays, with ␣ values two to three times higher in the batch compared to the column studies. This is in contrast to prior research, which has shown that bacterial transport is much greater under convective (column) conditions, compared to the quiescent conditions of a batch experiment (Medilanski et al, 2003;Rijnaarts et al, 1993). A possible explanation for the discrepancy is that the bacteria have a greater affinity for glass than for the sand grains, so hydrodynamics alone cannot account for the differences in retention behavior.…”
Section: Bacterial Retention In Batch and Column Assayscontrasting
confidence: 79%
“…This simplification was made because this reaction time resulted in a moderate number of bacterial cells per field, which could be easily and reproducibly counted under the microscope. In addition, the 120-min reaction time was modeled after similar experiments with Pseudomonas aeruginosa PAO1 and Desulfovibrio desulfuricans (ATCC 29577; Medilanski et al, 2003).…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…In this study, the cathodic protection categorized as the impressed current method type was applied to an artificial biofilm containing Pseudomonas aeruginosa (PAO1) (Medilanski et al, 2003) as a representative constituent of biofilm on carbon steel coupon. The effect of cathodic protection on bacterial viability in the biofilm was also investigated to clarify the biocidal mechanisms of cathodic protection.…”
Section: Introductionmentioning
confidence: 99%